Pharmacokinetic Study of Nalbuphine in Surgical Patients Undergoing General Anesthesia with Varying Degrees of Liver Dysfunction - Gao XN; Nie XY; Gao JL; Heng TF; Zhang YQ; Hua L; Sun YQ; Feng ZY; Wang MX; Jia L (Dove Medical Press, 2022)
Xiao-nan Gao,1 Xu-yang Nie,1 Jing-lin Gao,1 Tian-fang Heng,2 Yu-qi Zhang,2 Li Hua,1 Ya-qi Sun,1 Zhang-ying Feng,1 Ming-xia Wang,1 Li Jia2 1Department of Clinical Pharmacology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, People's Republic of China; 2Department of Anesthesiology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, People's Republic of ChinaCorrespondence: Ming-xia Wang, Department of Clinical Pharmacology, The Fourth Hospital of Hebei Medical University, 12 Jiankang Road, Shijiazhuang, People's Republic of China, Tel +86 311-66696233, Email mxia_wang@163.com Li Jia, Department of Anesthesiology, The Fourth Hospital of Hebei Medical University, 12 Jiankang Road, Shijiazhuang, People's Republic of China, Email 281575038@qq.comPurpose: This study aimed to characterize the pharmacokinetics of nalbuphine in patients undergoing general anesthesia with varying degrees of liver dysfunction.Patients and Methods: Twenty-four patients were enrolled and divided into three cohorts based on liver function: normal liver function (n = 13), mild liver dysfunction (n = 5), and moderate/severe liver dysfunction (n = 6). During the induction of anesthesia, they received 15 mg of nalbuphine intravenously. Venous blood samples were collected from each patient. The plasma concentration of nalbuphine was determined using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The pharmacokinetic parameters of nalbuphine were calculated by non-compartmental analysis (NCA) using Phoenix WinNonlin software.Results: Compared with the normal liver function group, the plasma elimination half-life (T1/2) of nalbuphine was increased by approximately 33% in the moderate/severe liver dysfunction group (2.66 h vs 3.54 h, P< 0.05), and the volume of distribution (Vd) increased by approximately 85% (100.08 L vs 184.95 L, P< 0.05). Multivariate analysis revealed that weight and platelet were associated with clearance (CL); total bilirubin as an independent factor was associated with T1/2, and weight associated with area under the curve (AUC(0→∞)) independently.Conclusion: The T1/2, mean residence time, and Vd of nalbuphine in patients with moderate/severe liver dysfunction were prolonged or increased significantly compared with those in the normal liver function group. These data suggest that it may need to be used with caution when nalbuphine is administered to patients with moderate or severe liver dysfunction.Keywords: nalbuphine, intravenous, liver dysfunction, UPLC-MS/MS, pharmacokinetics